The Effect of Ct Value with Length of Hospitalization of Covid-19 Pediatric Patients at RSPAD Gatot Soebroto and its Review according to Islamic View - Hanifah Azzahra Hedansa; Sri Hastuti Andayani; Firman Arifandi (Junior Medical Journal, 2023)
Introduction: COVID-19 is an infectious disease caused by SARS-CoV-2. There has been increased cases of COVID-19 in children in Indonesian became 11-12% with a mortality rate 0.6%. The gold standard for diagnose COVID-19 is using RT-PCR examination by used specimen from respiratory tract that are interpreted with Ct values (cycle threshold). Ct values can be interpreted as the level of viral load in patient. COVID-19 patient with low Ct values can have a risk poor prognostic. Therefore, it is important to know the effect of the Ct values with the length of stay of COVID-19 pediatric patients from a medical and Islamic perspective.Method: This type of research is analytic observational with a case control research design. The sample in this study were all COVID-19 pediatric patients who were hospitalized at RSPAD Gatot Soebroto during the period January - December 2021 who met the inclusion criteria of 66 respondents. Data collection is done by using secondary data in the form of medical records and processed it by used SPSS. Result: In this study, it was obtained from 66 respondents respondents, respondents with strong positive, positive, and weak positive Ct value each had an everage length of stay 11.8 days, 9.07 days, and 7.5 days. Based on the results of the bivariate analysis using the Kruskal Wallis alternative test, the p-value was 0.145 (0.05), so it can be said that H0 is accepted, which means that there is no significant relationship between Ct value and the length of stay of COVID-19 pediatric patients.Conclusion: There is no significant relationship between Ct values with the length of stay of COVID-19 children patients at RSPAD Gatot Soebroto.